Quality of internal audit and its impact on nature, timing and procedures of external audit An investigative study of a sample of external auditors Iraqi Solidary Companies for Auditing. - الكناني مجيد موسى (Journal of Economics and Administrative Sciences, 2020)
The study aims at investigating the quality of internal auditing and its impact on nature, timing, and procedures of external audit, based on international auditing standards, in particular ISA (610). The standard ISA (610) requires the external auditors to assess independence, the scope of internal audit unit, competence, and due professional care of internal auditors as indicators that reflect the quality of internal audit performance before deciding to rely on internal auditors. The sample of this study consisted of external auditors in Iraqi Solidary Companies for Auditing. A questionnaire was distributed to them via e-mail. the response rate was (70%) of the sample which reached (40) participants. Statistical analysis was carried out by using SPSS. The results of the research showed a statistically significant effect between elements of quality of internal audit and between nature, timing, and extent of external audit procedures in accordance with international audit standards. The scope of the internal audit unit’s work, and due professional care of internal auditors represent the most significant aspects of the quality of internal audit affect nature, timing, and procedures of external audit. External audit procedures are more affected by the quality of internal audits than the nature and timing of external audits. The researcher recommends strengthening the independence of internal audits and working to raise scientific and practical qualifications of internal auditors in order to increase their influence in nature, timing, and procedures of external audits.